The food preferences of five commercially important fishes of Gosthani estuary - Rao, L M; Sivani, G (Indian Journal of Fisheries, 2011)
The food and feeding habits of five species of commercially important fishes of the Gostham estuary (two mullets, one each of milk fish, sand whitings and silver biddies I have been studied. They exhibited food preferences according to their habitats. However, at times they were found to encroach upon other habitats and feed on a variety of food materials. This kind of feeding habit might have arisen because of the shallowness of the estuary, the depth of which is less than a foot at many places.